Circulating markers of prognosis and response to treatment in patients with midgut carcinoid tumours. Issue 11 (23rd March 2006) - Turner, G B; Johnston, B T; McCance, D R; McGinty, A; Watson, R G P; Patterson, C C; Ardill, J E S
Abstract : Background and aims: Midgut carcinoid tumours are uncommon tumours with an unpredictable clinical behaviour and few useful prognostic markers. Somatostatin analogues are widely used in treatment but a survival advantage has not been proven. We analysed features associated with poor prognosis and assessed the clinical implications of the biochemical response to therapy. Methods: Clinical and biochemical data were collected for patients with midgut carcinoid tumours attending a tertiary referral neuroendocrine clinic from 1978 to 2000. Using death as the end point, univariate and multivariate survival analyses were performed to identify prognostic indicators. The significance of altering biomarkers with therapy was also studied by including repeated measurements of the most prognostic biochemical parameter in a time dependent covariate survival analysis. Results: We identified 139 patients with sufficient data for our analyses. Factors associated with a poor outcome on univariate analysis included: plasma neurokinin A (NKA), urinary 5-hydroxyindolacetic acid output, age, and ⩾5 liver metastases. Plasma NKA was the strongest and only independent predictor of outcome on multivariate analysis. Patients in whom NKA continued to rise despite somatostatin analogues had a significantly worse survival than those in whom NKA stabilised or fell (one year survival rate 40% v 87%). Time dependent covariate analysis concluded that survival was better predicted by the most recent plasma NKA value rather than by the initial value. Conclusions: Plasma NKA is an accurate marker of prognosis for midgut carcinoid tumours. This is the first paper to support a survival advantage in patients in whom plasma NKA is altered by somatostatin analogues.